Policy-based QoS architecture in the IP multimedia subsystem of UMTS. - Wei Zhuang
The third-generation mobile system, or Universal Mobile Telecommunication System, will offer IP-based multimedia applications and services with end-to-end QoS guarantee. The key part providing these services is the policy-based QoS control architecture in the IP multimedia subsystem (IMS). In this tutorial we describe the network entities involved in the policy-based QoS architecture, their interactions to realize guaranteed QoS in the UMTS network, and the communication interfaces employed in the interactions.
Keywords: IMS; IP multimedia subsystem; UMTS; Universal Mobile Telecommunication System; Communication interfaces; Control architecture; End-to-end QoS guarantee; Network entity interactions; Policy-based QoS architecture; Services; Third-generation mobile system